Metformin and berberine synergistically improve NAFLD via the AMPK–SREBP1–FASN signaling pathway - Na Li; Quan-wei Chen; Xiao-long Gong; Fang Liu; Bin Zhang; Qi-shen Wang; Hao Zhang; Jian-jun Han (Scientific Reports)
Abstract Nonalcoholic fatty liver disease (NAFLD) is a prevalent metabolic condition linked to dyslipidemia, insulin resistance, and persistent inflammation. Due to its complex pathogenesis, no approved pharmacological treatments currently exist. The research sought to explore the combined impact of metformin (Met) and berberine (BBR) on NAFLD, focusing on the AMPK–SREBP1–FASN pathway implicated in liver lipid regulation. The study design incorporated in both living organisms and laboratory conditions to examine how these interventions influenced NAFLD-associated metabolic abnormalities. The HFD-fed mice provided insight into systemic effects, while the OA/PA-stimulated HepG2 cells offered a controlled environment to investigate cellular mechanisms. By employing this dual approach, the researchers could thoroughly characterize the efficacy of Met, BBR, and their combination in mitigating metabolic disturbances. An Adenosine 5‘-monophosphate (AMP)-activated protein kinase(AMPK) inhibitor was used in cellular experiments to verify the AMPK-dependent mechanism. Our findings highlight that compared to monotherapies, combination treatment significantly enhanced AMPK activation and inhibited sterol regulatory element-binding protein 1 (SREBP1) expression and that of its downstream target fatty acid synthase (FASN). In HepG2 cells, these effects were partially reversed by the AMPK inhibitor, confirming AMPK dependence. In vivo, the combined therapy effectively inhibited body weight gain, reduced visceral fat accumulation, improved insulin sensitivity, and attenuated hepatic steatosis and inflammation. The combination of metformin and berberine exerts synergistic effects in ameliorating NAFLD by activating AMPK, downregulating SREBP1 and FASN, and improving lipid metabolism. These findings provide evidence supporting a potentially effective multi-modal treatment approach for NAFLD.